THE CONSTRUCTION OF SANTOSH CULTURAL IDENTITY IN ONE OUT OF MANY BY V.S NAIPAUL - FIRDAUSIAH, ZAHRA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: cultural identity, ambivalence, postcolonialismSince Indian people gained their freedom in 1947, many of them have migrated to other countries. The migration creates an identity crisis. It is because the original culture which is brought from the homeland is very different from the new culture in new environment. The differences of both cultures make an Indian diaspora confused to which cultural identity they practice and maintain. In one hand, an Indian diaspora want to adapt the new culture. On the other hand, an Indian diaspora want to maintain their original culture. In this case an Indian diaspora experience the ambivalence. This research is aimed to reveal  Santosh’s ambivalences in One Out OfMany by V.S Naipaul and how he constructs his cultural identity.This research uses qualitative method and employs two concepts, namely ambivalence and cultural identity with postcolonial approach. The result shows someambivalences within Santosh. Ambivalence happens in aspect of values, belief, andthe using of currency. Besides, this research reveals how Santosh constructs his cultural identity by combining and negotiating both cultures, and how he getsdressed.The writer suggests the next researchers to use the biographical approach and compare One Out Of Many story with other works by V.S Naipaul, because most ofhis works portray identity crisis and cultural identity construction. The researcher canbe focused on why most of his works are related to  those topics.